2013
DOI: 10.1111/jog.12259
|View full text |Cite
|
Sign up to set email alerts
|

Tramadol versus fentanyl during propofol‐based deep sedation for uterine dilatation and curettage: A prospective study

Abstract: Tramadol provides similar analgesic efficacy to fentanyl. Furthermore, tramadol may provide better respiratory stability in patients undergoing a D&C procedure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 11 publications
0
5
0
6
Order By: Relevance
“…La duración del procedimiento de legrado uterino es de 12 ± 2,9 minutos, considerando que somos un centro de enseñanza y contamos con residentes de gineco-obstetricia en fase de entrenamiento; en este sentido, Tas y col 9 indican un tiempo del procedimiento de 5,7 ± 2,6 minutos más corto comparado al presente estudio, por los factores previamente resaltados.…”
Section: Discussionunclassified
“…La duración del procedimiento de legrado uterino es de 12 ± 2,9 minutos, considerando que somos un centro de enseñanza y contamos con residentes de gineco-obstetricia en fase de entrenamiento; en este sentido, Tas y col 9 indican un tiempo del procedimiento de 5,7 ± 2,6 minutos más corto comparado al presente estudio, por los factores previamente resaltados.…”
Section: Discussionunclassified
“…Opiods that are used for analgesia are not common in day-case procedures because it causes respiratory depression, itching, and has long-lasting recovery period (11). In this study, we compared tramadol and ketamine which are similar in terms of analgesic efficacy and both have short recovery periods.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to this, side effects of this agent such as nausea and vomiting are mentioned (10). In the study conducted by Taş et.al (11), propofol-fentanyl and propofol-tramadol were compared in patients that had dilatation and curettage. Researchers have found similar analgesic features, but they concluded that tramadol had less effect on respiration and so it could be safe.…”
Section: Discussionmentioning
confidence: 99%
“…Dikatakan bahwa tramadol memiliki potensi analgesi yang sama dengan 1/1.000 fentanil. 4 Penelitian tramadol sebagai analgetik intraoperatif pada operasi abdomen dengan dosis per kgBB sebesar 2 mg, 3 mg, dan 4 mg menunjukkan pengaruh yang sama terhadap tekanan darah dan laju nadi, tetapi dosis 4 mg/kgBB memiliki efek analgesi sampai lima jam postoperasi. 5 Tujuan penelitian ini adalah mengetahui perbandingan antara tramadol 2 mg/kgBB dan fentanil 2 µg/kgBB sebagai nalgetik intraoperatif, dilihat dari pengaruhnya terhadap skor PRST pada operasi laparotomi ginekologis.…”
Section: Pendahuluanunclassified